Management of herpangina: a viral infection in infants - Prathiwi, Caecilia Dewi Ratna; Bramanti, Indra (Faculty of Dentistry, Universitas Gadjah Mada, 2023)
Herpangina is a self-limiting disease caused by coxsackievirus. The manifestation consists of acute febrile with small ulcerative or vesicular lesions on the tonsillar, soft palate, uvula and buccal mucosa. The disease mostly affects children. The aim of this case report is to discuss the oral symptoms of herpangina based on current literature for dental and health practitioners. In our case, a 15-month-old baby girl presented with high fever reaching 40.2 °C for 2 days with no seizures, cold and cough. Intra oral examination showed several well-defined whitish round lesions on the soft palate and one on the upper left lip. The patient was prescribed 3ml of methisoprinol 250 mg 3 times a day, 4 ml of paracetamol 125 mg every 6 hours, hyaluronic acid spray 3 times a day, and 1ml of vitamin C 40 mg taken once a day. The patient showed no sign of bacterial infection. Lesion disappeared after 7 days of treatment. Upon follow-up visit after 2 weeks, the lesion had completely disappeared. Dentists should be able to recognize and manage herpangina cases in infants.